A novel hybrid additive and subtractive manufacturing method of carbon fiber reinforced peek with enhanced strength - Taijun He; Dong Yang; Han Chen; Xuezhi Fu; Lu Yang; Yu Tao; Ji Xiong; Junbo Liu (Journal of Materials Research and Technology)
In this study, cold deposition-based high-temperature fused deposition modeling 3D printing followed by coated tool machining were employed to process CFRP samples. The types of coated tools, their microstructures, properties, as well as the surface conditions, morphologies, and properties of the machined CFRP were investigated. The results indicated that the AlTiN/TiN coating on the (VHfTaTi)C substrate has the greatest thickness and its columnar structure is notably less distinct. The coating deposited on the (NbHfTaTi)C substrate has the highest hardness, reaching 3296 HV. For the hybrid additive and subtractive manufacturing samples, the shear strength of hybrid additive and subtractive manufacturing samples show a shear strength of 32 MPa which is twice that of additive manufacturing specimens, nearly 15 MPa. PEEK is a semi-crystalline polymer, in which the molecular chains are tightly and orderly arranged in the crystalline regions, while they are loosely and disorderly arranged in the amorphous regions. During the cutting process, the temperature of machining surface would increase a lot, and the crystallinity of the polymer would be enhanced at the same time. Increasing the crystallinity means that the proportion of orderly arranged molecular chains in the material is enhanced. Thus the strength was improved.